Ecological Assessment of Fish Assemblage For East AL-Hammar Marshe , North of Basrah, Iraq by using Integrated Biological Index (IBI) - C.J. AL-Shamary , A.; K. AL-Zawar, J.; H. Younis, K. (University of Thi-Qar Journal of Science, 2009)
The Present study was included the ecological assessment of–East Al-Hammar marsh theperiod November, 2006 to November, 2007, The samples were collected monthly for two stationsstudy, Al-Nagarah and Burgah fifteen metrics were chosen to calculate Integrated Biological Index(IBI) depending on the following major categories The first category (species richness) isrepresented by the total number of native, alien and migrations. The second major category (fishspecies composition) includes seven metrics, the percent of individuals that are considered assensitive native species (metric one) the second metric represents the percent of individuals of alienspecies. The percent of individuals that are considered as sensitive migration species was the thirdmetric, while the forth metric was the percentage of tolerant species. The Fifth metric was thepercent of individuals of Carassius auratus. The sixth metric represented by the percentage of Lizaabu while seventh metric include the diversity index (H). The third major category included fifth oftrophic guild metrics which is Composed of the percent of individuals that are considered asomnivores, carnivores, detrivores, herbivorous, and the native top predators. (IBI) values of AlHammar marsh of studying stations were evaluated to be impaired (<60). Throughout the studytime, except December and May in the first station, June and July in the second station whichevaluate to be marginally impaired 60-80 June, July, August, September in the first station and August, September in the second station, evaluated to be accepted (>80).